Instability of Styrene/Polystyrene/Polybutadiene/Polystyrene-beta-Polybutadiene Emulsions that Emulate Styrene Polymerization in the Presence of Polybutadiene - Velasquez, Eliezer (2013)
This paper investigates the room-temperature demixing of oil-in-oil emulsions containing styrene (St), polybutadiene (PB), a St-butadiene star block copolymer (BC), and 2 polystyrene (PS) samples of different molecular weights; and is a contribution towards a better understanding of the stability/ instability of the reaction mixture in a bulk high impact polystyrene (HIPS) process close to the phase inversion. Twelve bulk prepolymerizations of St in the presence of PB were emulated, at 10, 15, and 20% conversion; and with constant grafting efficiencies. All the blends contained 6% in weight of butadiene units. After stirring the blends for 24 h, the decantation demixing process was monitored along 30 days, with daily measurement of the interface levels after appearance of a clear interface. All final samples exhibited an upper (PB-rich) phase and a lower (PS-rich) phase. Additionally, the experiments with the high molar mass PS and high grafting efficiencies also exhibited a third intermediate BC-rich phase. For some of the isolated phases, their unswollen morphologies were observed by TEM, and the St partition coefficient was gravimetrically determined. All the isolated phases exhibited macrophase separation into homopolymer- and copolymer-rich macrodomains, with lamellar microdomains in the copolymer-rich macrodomains. The BC showed a greater affinity towards the PS-rich phase. The separation of an independent BC-rich phase in the blends containing the high molar mass PS and at high grafting efficiencies, modifies the idea of the graft- or block copolymer molecules located at the interface of large PS-rich and PB-rich phases.